Posterior corneal surface and anterior chamber changes after Small incision lenticule extraction and Femtosecond laser‐assisted laser in‐situ keratomileusis - Lijie Xie; Shanqing Zhu; Guanrong Wu; Changting Tang; Yunxiang Guo; Honghua Yu; Yijun Hu (MedComm – Future Medicine, 2023)
Abstract We aimed to evaluate the posterior corneal and anterior chamber changes following small incision lenticule extraction (SMILE) and femtosecond laser‐assisted laser in situ keratomileusis (FS‐LASIK). This retrospective study included 93 eyes for SMILE and 228 eyes for FS‐LASIK. Posterior corneal curvature, anterior chamber biometrics, and posterior corneal aberrations preoperatively and at 1 week and 3 months after surgery were evaluated. The correlation between surgical‐related factors and posterior corneal morphology changes, posterior corneal morphology changes, and posterior corneal aberration alterations were determined. There was an increase in mean posterior corneal radius (PCC R) and flat posterior corneal radius (PCC R1) and decrease in anterior chamber depth and anterior chamber volume in the SMILE and FS‐LASIK group (all p < 0.05). A significant difference was observed in posterior corneal higher‐order aberrations before and after the FS‐LASIK (p = 0.006). A negative correlation was found between alterations of PCC R and changes of posterior corneal spherical aberrations in the SMILE (r = −0.289) and FS‐LASIK group (r = −0.383). In conclusion, posterior corneal and anterior chamber biometrics are changed after SMILE and FS‐LASIK. Innovatively, we find that changes in posterior corneal morphology are correlated with posterior corneal aberration alterations.